1996
DOI: 10.1088/0953-8984/8/38/006
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies in the ion transport of phosphoric acid in water and heavy-water environments

Abstract: This paper presents the experimentally determined precise transport data - (tracer) diffusion coefficients in both water and heavy-water environments, together with molar conductivity and viscosity of (ortho)phosphoric acid in water over an extended concentration range at [Formula: see text]. The concentration (c) dependence of the diffusion coefficients (D), viscosity [Formula: see text] and molar conductivity [Formula: see text] have been analysed. An anomalous depression in the D - [Formula: see text] curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…For example, concentrated phosphoric acid electrolytes have unusually high conductivity given their high viscosity. In addition, diffusion coefficient measurements for both protons and phosphorus-containing species exhibit unusual concentration and temperature dependence [16,17]. The relative invariance with electrolyte composition of the diffusion coefficients in Table 1 reinforces the conclusion that concentrated phosphoric acid is not a hydrodynamically simple fluid.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…For example, concentrated phosphoric acid electrolytes have unusually high conductivity given their high viscosity. In addition, diffusion coefficient measurements for both protons and phosphorus-containing species exhibit unusual concentration and temperature dependence [16,17]. The relative invariance with electrolyte composition of the diffusion coefficients in Table 1 reinforces the conclusion that concentrated phosphoric acid is not a hydrodynamically simple fluid.…”
Section: Resultssupporting
confidence: 61%
“…However, previous authors have noted that the transport properties of concentrated phosphoric acid are anomalous, and they have suggested that transport cannot be described by the prototypical hydrodynamic model of slip-free particle motion through a liquid, or in other words, by the Stokes-Einstein equation [16,17]. For example, concentrated phosphoric acid electrolytes have unusually high conductivity given their high viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…The limitation of using this model is that the predicted effective radius of the solute is not the physical dimension. From the modified Levich analysis of the data an effective radius of 1.9-2.9 · 10 -9 m is obtained, which is an order of magnitude larger than expected for a water molecule with an O-H bond length of approximately 0.1 · 10 -9 m. This agrees with the complex behavior of the concentrated phosphoric acid system as suggested by Chakrabarti [10] and Chung [11]. In effect, due to the electrostatic interactions between water and the electrolyte bath, the effective diffusivity is an order of magnitude less than the StokesEinstein model predicts for a hard sphere model.…”
Section: Validity Of the Stokes-einstein Modelsupporting
confidence: 85%
“…Other authors [10,11] have proposed that the concentrated phosphoric acid/water system is not a hydrodynamically simple fluid. The hard sphere and simple fluid assumptions used in the Stokes-Einstein relationship suggest the equation does not physically model the diffusion of water in the phosphoric acid system.…”
Section: Modified Levich Analysismentioning
confidence: 99%
“…1,2) Moreover, in spite of its high viscosity, liquid phosphoric acid has high proton conductivity, which makes it useful as fuel cell electrolytes. Therefore, many experimental and theoretical studies have been carried out on the liquid phase [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] as well as on the monomer [21][22][23] ( Fig. 1), crystal, [24][25][26] and the polymeric gels [27][28][29][30] of phosphoric acid.…”
Section: Introductionmentioning
confidence: 99%